Exploring the potential to use data linkage for investigating the relationship between birth defects and prenatal alcohol exposure - O'Leary, Colleen Marie; Elliott, E.; Nassar, N.; Bower, C. (John Wiley & Sons, Inc., 2013)
Background: This study explores the potential of data linkage to investigate the proportion of birth defects classified as alcohol-related (ARBD) by the Institutes of Medicine (IOM) that are attributable to maternal alcohol-use disorder. Methods: Maternal alcohol-use disorder was identified using International Classification of Diseases (9th and 10th revision) codes for alcohol-related diagnoses recorded on record-linked Western Australian health, mental health, and/or drug and alcohol datasets 1983 to 2007. Children of these mothers (n = 23,859) were compared with a randomly selected cohort of children born to mothers without an alcohol diagnosis, frequency-matched by maternal age, Aboriginal status, and child’s birth year (n561,370). Birth defects were identified through linkage with the Western Australian Register of Developmental Anomalies and defects with chromosomal causes were excluded. Associations between overall and individual IOM-designated ARBD and a maternal alcohol-related diagnosis recorded “during pregnancy” or “any” diagnosis (before/during/after pregnancy) was assessed using multivariate logistic regression to generate odds ratios and 95% confidence intervals. Population-attributable fractions were calculated for significant results using total population numbers.Results: There was a significant association between maternal alcohol-related diagnoses recorded during pregnancy and ARBD (adjusted odds ratio, 3.14; 95% confidence interval, 2.49–3.96), with an attributable fraction of 0.57%. “Any” maternal alcohol diagnosis demonstrated a higher attributable fraction for ARBD (1.53%), with the highest attributable fractions for microcephaly (7.31%), ptosis (3.75%), atrial septal defect (2.86%), and conotruncal heart defects (2.01%). Conclusion: Research using linked, population-based administrative health data has the potential to advance knowledge of ARBD. Routine collection and recording of alcohol use during pregnancy for all pregnant women is required and would enhance this methodology.